2019
DOI: 10.1177/1090198119869964
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Text Message Navigation Program Improves the Show Rate for Outpatient Colonoscopy

Abstract: Background. Numerous barriers to outpatient colonoscopy completion exist, causing undue procedure cancellations and poor bowel preparation. We piloted a text message navigation program to improve colonoscopy adherence. Method. We conducted a prospective study of patients aged 18 to 75 years scheduled for outpatient colonoscopy at an urban endoscopy center in April 2018. An intervention arm consisting of bidirectional, automated text messages prior to the procedure was compared with a usual care arm. We enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 13 publications
0
43
1
Order By: Relevance
“…The results of randomized clinical trials often do not confirm pilot findings; in the pilot study 11 for this trial, we observed a significant increase in appointment adherence among patients receiving a texting intervention. There may be several reasons for this discrepancy, some of which represent a type of generalizability bias that may occur in transition from pilot to randomized clinical trial.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The results of randomized clinical trials often do not confirm pilot findings; in the pilot study 11 for this trial, we observed a significant increase in appointment adherence among patients receiving a texting intervention. There may be several reasons for this discrepancy, some of which represent a type of generalizability bias that may occur in transition from pilot to randomized clinical trial.…”
Section: Discussioncontrasting
confidence: 75%
“…We conducted a quality improvement pilot study that evaluated the feasibility of a 1-week text messaging protocol for patients who were scheduled for outpatient colonoscopy. 11 Among 21 patients enrolled in the pilot study, there was high user acceptability and higher colonoscopy attendance rates compared with baseline values at an urban academic endoscopy center. The aim of this study was to evaluate the effect of an automated text message–based intervention on appointment adherence and bowel preparation quality in a larger, randomized setting.…”
Section: Introductionmentioning
confidence: 97%
“…In our case, there were also time windows for submission so that only a single piece of information (ie, BP or medication adherence) was being collected at a time. This simplified approach makes automated texting technically feasible and approachable across many clinical settings [ 17 , 22 - 24 ]. Because texting is a largely unrestricted platform, automating a response to correct unstandardized submissions is a way to train users to conform with the program.…”
Section: Discussionmentioning
confidence: 99%
“…In the original study, scheduled automated text messages were used to (1) monitor each patient’s BP measurements over time, (2) provide intermittent encouragement for engaging behavior, and (3) monitor BP medication adherence. Texts were sent through Way to Health, a Health Insurance Portability and Accountability Act–compliant, bidirectional, automated text communication platform used to engage with patients for research studies and clinical care delivery [ 17 , 18 ]. Patients in the original study received a variety of outbound texts including information about the study and upcoming in-person study visits.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a pilot study by these authors of a nearly identical text intervention yielded improved colonoscopy show rates. 4 Additionally, numerous other studies have found text messaging to be effective for appointment attendance. 5 Second, with colonoscopies already in high demand (and demand expected to increase), interventions to reduce nonattendance are critically needed.…”
mentioning
confidence: 99%